Bordskultur och glashandel i renässansens Nordeuropa - Haggrén, Georg (Hikuin, 2010)
Table manners and the trade of glass in the Northern Europe during the Renaissance By Georg Haggrén During the Renaissance, the use of glass increased quickly everywhere in western, central and northern Europe. In the Middle Ages glass vessels were exclusive items used by nobles and the most prosperous merchants. In the early modern era glass vessels came into the hands of not only the poorer townspeople but also some of the peasants too. At the same time table manners improved and people increasingly started to use different vessels for different drinks. The Passgläser were usually octagonal green beakers which were made in northern Germany, the Netherlands, and even in southern Scandinavia. Early modern glass of the Berkemeyer and Römer variety were produced especially in the Rhineland and the Netherlands. From 16th and 17th century paintings we can see that Berkemeyer and Römer glasses were meant for white wine and Passgläser especially for beer. In the second half of the 16th century Venetian glass started to gain ground in the markets of western and central Europe. Soon many Italian glass blowers left their homes and started to make glass in western and central Europe. The »cristallo« or the façon de Venice -glasses made by these Italian masters soon became popular in all of the western and northern Europe. During the Renaissance, material culture became uniform with regard to both ceramics and glass vessels in all of the northern Europe. Similar Passgläser, Römerglas and façon de Venice winged goblets were used in Denmark, Norway, Sweden and Finland alike.